2012
DOI: 10.1590/s1678-77572012000600005
|View full text |Cite
|
Sign up to set email alerts
|

Push-out bond strength and SEM evaluation of a new bonding approach into the root canal

Abstract: ObjectiveThis study evaluated the performance of different adhesive systems in fiber post placement aiming to clarify the influence of different hydrophobic experimental blend adhesives, and of one commercially available adhesive on the frictional retention during a luting procedure. Material and MethodsOne luting agent (70 Wt% BisGMA, 28.5% TEGDMA; 1.5% p-tolyldiethanolamine) to cement fiber posts into root canals was applied with 4 different adhesive combinations: Group 1: The etched roots were rinsed with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…20 This technique has been shown to produce adhesive interfaces with higher bond strength, reduced interface nanoleakage, and increased stability over time when compared to the "water-wet bonding technique." 21,22 In endodontics, it is suggested that a final rinse of dentin walls with different substances 23 or with ethanol may alter root dentin properties, enhancing endodontic sealer penetration into dentinal tubules. 24,25 The interaction between a hydrophobic sealer and a surface with higher hydrophobic characteristics would provide a low contact angle, higher sealer penetration, greater mechanical interlock into the tubules, retention, sealing ability and, consequently, in vivo antibacterial effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…20 This technique has been shown to produce adhesive interfaces with higher bond strength, reduced interface nanoleakage, and increased stability over time when compared to the "water-wet bonding technique." 21,22 In endodontics, it is suggested that a final rinse of dentin walls with different substances 23 or with ethanol may alter root dentin properties, enhancing endodontic sealer penetration into dentinal tubules. 24,25 The interaction between a hydrophobic sealer and a surface with higher hydrophobic characteristics would provide a low contact angle, higher sealer penetration, greater mechanical interlock into the tubules, retention, sealing ability and, consequently, in vivo antibacterial effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ethanol solution was used to condition the root canal prior to filling 8 or bonding 14 , instead of dehydrating the dentine using a technique known as 'ethanol wet-bonding'. Conditioning of the dentine promotes a surface with hydrophobic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol solution is a dehydrating agent 10 that has been tested to improve dentine wettability and to increase sealer penetration along the root canal walls 8 . Some authors suggest there is a higher compatibility between ethanol-saturated dentine and hydrophobic resin monomers, preventing collagen shrinkage and allowing for higher impregnation 11 , infiltrating hydrophobic monomers into the demineralised dentine collagen matrix [12][13][14] . The use of 70% or 100% ethanol increased dentine wettability and improved the interaction between resin-based endodontic sealer and dentine root canal walls 15 .…”
Section: Introductionmentioning
confidence: 99%
“…For the post loading, three different punch pins with diameters of 0.8 mm, 1.0 mm, and 1.2 mm were used for the apical, middle, and coronal samples, respectively. The posts inside the specimens were loaded on the apical to coronal direction 27. The maximum failure load was measured in newtons (N) and divided by the bonding surface calculated using a formula of conical frustrum to obtain the bond strengths 20,21…”
Section: Methodsmentioning
confidence: 99%